Neurosarcoidosis - Agnihotri, Shruti P.; Singhal, Tarun; Stern, Barney J.; Cho, Tracey A. (Seminars in Neurology, 2014)
Sarcoidosis is an idiopathic multisystem granulomatous disorder. Neurologic manifestations in sarcoidosis are varied and making a diagnosis of neurosarcoidosis can be difficult as it mimics various other neurologic diseases. Knowledge of the syndromes associated with neurosarcoidosis can help guide the diagnostic evaluation. Definitive diagnosis requires neurologic tissue evidence of noncaseating granuloma, but in practice probable diagnosis is often made through nonneurologic biopsy and a characteristic syndrome and imaging. Treatment remains empiric, but new advances in immunologic therapy hold promise for effective and less-toxic regimens.
Keywords: sarcoidosis; neurologic complications; neurosarcoidosis; cranial neuropathy; aseptic meningitis; granuloma; myelitis